Novel roles for factor XII-driven plasma contact activation system - Müller, Felicitas; Renné, Thomas (Current opinion in hematology, 2008)
Blood coagulation is a tightly regulated process, involving vascular endothelium, platelets, and plasma coagulation factors. Formation of fibrin involves a series of sequential proteolytic reactions, initiated by the 'extrinsic' and 'intrinsic' pathway of coagulation. As hereditary deficiency of factor XII, the protease that triggers the intrinsic pathway and the kallikrein-kinin system, is not associated with a bleeding disorder or other disease states, the physiological role of factor XII is unknown. Patient studies, genetically altered mouse models, and plasma assays analyzed functions of the factor XII-driven contact activation system for coagulation and inflammation. This review focuses on articles, which report phenotypization of animals deficient in the contact system proteins factor XII, factor XI and high-molecular-weight kininogen, as well as novel links between factor XII and edema formation, discovery of new in-vivo activators of factor XII, and functions of the factor XII downstream protease factor XI. Recent studies improved understanding of the factor XII-driven contact system in hemostasis, thrombosis, and inflammation. Studies in mouse models revealed that deficiency in contact system proteins protects from arterial thrombus formation, but does not affect hemostasis. Targeting contact system proteins offers new opportunities for safe anticoagulation associated with minimal bleeding risk. Furthermore, targeting factor XII activity provides an opportunity to treat edema formation.